Invention and open innovation processes, and linkages: A conceptual framework - Syed Muhammad Ali Tirmizi; Qaisar Ali Malik; Syeda Sheeba Hussain (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
A conceptual model has been developed to present comprehensively the processes and linkages of invention and open innovation for those knowledge workers who want to transform idea of a new product or service into a reality. The progression of idea conceptualization, realization and marketing is further divided into two phases; first is invention and second is open innovation. These phases are integrated into a complex framework representing a comprehensive flowchart which provides a snapshot of gradual transition of invention processes into open innovation processes. The conceptual model rests on existing literature that methodologically connects access to finance, funding constraints, cognitive and social dimensions, skills, mental model, conceptual knowledge and knowledge production capacity of the scientists (i.e., knowledge worker), scope and pioneering of the invention, technological infrastructure, collaboration with private firms and universities and utilization of digital technologies. The invention, as well as open innovation activities, are discussed with respect to World Intellectual Property Organization and Global Innovation Index country rankings and the number of patents filed and granted to the world including Pakistan. The framework is a rigorous but rewarding process for a knowledge worker who designs and develops a new product, process, procedure, mechanism and methodology to serve humanity and the marketplace.
Keywords: 650; open innovation; conceptual model; Invention; knowledge worker; market; novel idea